Adat, Authority, and Agribusiness: The Struggle for Customary Land in Salareh Aia Agam Regency - Edi Indrizal; Ermayanti; Ade Irwandi (Soshum: Jurnal Sosial dan Humaniora, 2025)
This article examines the intricate relationship between the expansion of oil palm plantations and the preservation of customary (adat) systems in the villages of Salareh Aia Utara and Salareh Aia Barat, Agam Regency, West Sumatra. Employing a critical ethnographic approach, the study investigates how customary land, traditionally managed by Ninik Mamak (traditional leaders), has been transferred to private companies—particularly PT AMP Plantation—through adat-based agreements and compensation mechanisms. The research highlights the emergence of internal conflicts among traditional leaders, disputes over authority and compensation, and broader tensions between indigenous communities and corporate interests. Findings reveal that the process of land transfer, while formally adhering to customary and legal procedures, often leads to contestation, fragmentation of community leadership, and persistent disputes over land rights and plasma distribution. The article highlights the intricate interplay of economic, social, and political factors that influence these dynamics, underscoring the need for companies and policymakers to acknowledge the evolving nature of customary authority and the importance of culturally sensitive engagement. Ultimately, the study contributes to a deeper understanding of how modernisation and agribusiness intersect with indigenous rights and social structures in contemporary Minangkabau society.